Roaming is the dominant mechanism for molecular products in acetaldehyde photodissociation. - Heazlewood, B; Jordan, M; Kable, S; Selby, T; Osborn, D; Shepler, B; Braams, B; Bowman, J (2008)
Reaction pathways that bypass the conventional saddle-point transition state (TS) are of considerable interest and importance. An example of such a pathway, termed "roaming," has been described in the photodissociation of H(2)CO. In a combined experimental and theoretical study, we show that roaming pathways are important in the 308-nm photodissociation of CH(3)CHO to CH(4) + CO. The CH(4) product is found to have extreme vibrational excitation, with the vibrational distribution peaked at approximately 95% of the total available energy. Quasiclassical trajectory calculations on full-dimensional potential energy surfaces reproduce these results and are used to infer that the major route to CH(4) + CO products is via a roaming pathway where a CH(3) fragment abstracts an H from HCO. The conventional saddle-point TS pathway to CH(4) + CO formation plays only a minor role. H-atom roaming is also observed, but this is also a minor pathway. The dominance of the CH(3) roaming mechanism is attributed to the fact that the CH(3) + HCO radical asymptote and the TS saddle-point barrier to CH(4) + CO are nearly isoenergetic. Roaming dynamics are therefore not restricted to small molecules such as H(2)CO, nor are they limited to H atoms being the roaming fragment. The observed dominance of the roaming mechanism over the conventional TS mechanism presents a significant challenge to current reaction rate theory.